The relationship between characteristics and patient satisfaction in complementary services by midwives - Setyaningsih, Dewi; Novika, Almira Gitta; Angelika, Marseli Dwi (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Midwifery care has been combined with alternative and complementary midwifery services. The increase in complementary services needs to be balanced with efforts to improve the quality of medical services, one of which is assessing patient satisfaction.Objective: to determine the relationship between patient characteristics and satisfaction with complementary services by midwives.Methods: This research was a quantitative study using a cross-sectional design. The research location was Ngaglik I Public Health Care area. The sample of this study amounted to 30 respondents taken by purposive sampling. Data analysis using univariate and bivariate chi-squareResults: There is no relationship between age and patient satisfaction (P-value 1.00>0.05). There is no relationship between employment status and patient satisfaction (P-value 0.657>0.05). Based on the level of education, there is no relationship with patient satisfaction (P-value 0.637>0.05). There is no relationship between parity (P-value 1.00>0.05) with patient satisfaction in complementary services by midwives.Conclusion: There is no relationship between the characteristics of age, occupation, education, and parity with patient satisfaction in complementary services by midwives.